Pengaruh Profitabilitas, Manajemen Risiko dan Manajemen Modal Kerja terhadap Return Saham pada Perusahaan Apparel & Luxury Goods di BEI - Herni Viviana Sari; Abdul Hadi (Journal of Management and Business, 2025)
This research aims to examine and analyze (1) the effect of Return On Asset (ROA) on stock returns of Apparel & Luxury Goods companies listed on the IDX from 2018-2022, (2) the effect of Return On Equity (ROE) on stock returns of Apparel & Luxury Goods companies listed on the IDX from 2018-2022, (3) the effect of Beta on stock returns of Apparel & Luxury Goods companies listed on the IDX from 2018-2022, and (4) the effect of Cash Conversion Cycle (CCC) on stock returns of Apparel & Luxury Goods companies listed on the IDX from 2018-2022. The type of research is causal/associative using a quantitative approach. The population in this study consists of all Apparel & Luxury Goods companies listed on the IDX for the period 2018-2022, totaling 23 companies. The research sample was selected through purposive sampling, resulting in 9 companies that met certain criteria. This study uses multiple linear regression data analysis techniques with the SPSS software. The research results show that Return On Assets (ROA) and Cash Conversion Cycle (CCC) have an impact on stock returns in the Apparel & Luxury Goods industry listed on the IDX for the period 2018-2022. Meanwhile, Return On Equity (ROE) and stock Beta do not have an effect on stock returns in the Apparel & Luxury Goods industry listed on the IDX for the period 2018-2022.